2007
DOI: 10.1111/j.1863-2378.2007.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Prudent Antibiotic Use on Dairy Farms in South Carolina: A Pilot Project on Farmers’ Knowledge, Attitudes and Practices

Abstract: Inappropriate use of antibiotics in humans and animals contributes to decreased antimicrobial susceptibility in bacteria of medical importance. Resistant bacteria being transferred from animals to humans are causing public health concern. In-person interviews were conducted with 20 dairy farmers in rural counties of South Carolina to determine farmers' knowledge and attitudes about prudent antibiotic use among livestock. Four focus groups (n = 22) were also conducted to ascertain farmers' specific information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(163 citation statements)
references
References 23 publications
14
147
1
1
Order By: Relevance
“…Several authors have stressed the importance of preventive strategies to reduce diseases and antibiotic use in farm animals, the important role of veterinarians as partners for farmers herein and the importance of a comprehensive animal health planning strategy with farmers' compliance on individual farms (Brennan and Christley, 2013;Friedman et al, 2007;Cattaneo et al, 2009;LeBlanc et al, 2006). Financial and practical (time) restrictions or the perceived insufficient return on investment as found in our study, are known important reasons for farmers not to implement preventive measures (Derks et al, 2013;Friedman et al, 2007;Laanen et al, 2014;Wierup, 2000;Leach, 2008;Coyne et al, 2014), which is supported by our findings.…”
Section: Veterinary Advices and Farmers' Compliancementioning
confidence: 99%
“…Several authors have stressed the importance of preventive strategies to reduce diseases and antibiotic use in farm animals, the important role of veterinarians as partners for farmers herein and the importance of a comprehensive animal health planning strategy with farmers' compliance on individual farms (Brennan and Christley, 2013;Friedman et al, 2007;Cattaneo et al, 2009;LeBlanc et al, 2006). Financial and practical (time) restrictions or the perceived insufficient return on investment as found in our study, are known important reasons for farmers not to implement preventive measures (Derks et al, 2013;Friedman et al, 2007;Laanen et al, 2014;Wierup, 2000;Leach, 2008;Coyne et al, 2014), which is supported by our findings.…”
Section: Veterinary Advices and Farmers' Compliancementioning
confidence: 99%
“…Indeed, in a study which explored farmers' knowledge and attitudes towards antimicrobial usage in livestock, a lack of knowledge about antimicrobials and bacterial resistance was highlighted (Friedman et al, 2007). For example, it was found that farmers mostly relied on their own or a neighbour's experience rather than scientific evidence or advice from their veterinarian to decide which treatment to adopt.…”
Section: Introductionmentioning
confidence: 97%
“…Though veterinarians were the main source of information, limited finances for expenditure on veterinary support was a key barrier to seeking out antibiotic protocols (Friedman et al, 2007). If factors other than those directly related to the effective treatment of disease (whilst minimizing the emergence of resistance) have a large impact on the eventual therapy selected and subsequently applied, then these factors (e.g., marketing, price, availability, neighbour's experience) are potentially an important issue to consider.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study evidenced that 100% farmer had no idea about antimicrobial resistance and withdrawal period of antibiotics, whereas a study in New Zealand showed the majority (79%) of farmers understood that there is a risk of developing antimicrobial resistance (McDougall et al, 2017) here is far variation of these findings with our, because only 47% farmer's knowledge had at primary education level and 40% farmers were illiterate. A study in South Carolina showed that over 40% of farmers were very familiar with antibiotic resistance and were confident in their use of antibiotics and their participants had high school (42.9%, n = 18) or undergraduate college (45.2%, n = 19) education (Friedman et al, 2007).…”
Section: Anthropological View Of Goat Owners'mentioning
confidence: 99%
“…Farmers' knowledge is another important determinant to chase the problem of antibiotic resistance (Friedman et al, 2007). In Chittagong, many goat farmers have primary educational background.…”
Section: Introductionmentioning
confidence: 99%